Numerical Optimization of Drilling Parameters for Gas Predrainage and Excavating-Drainage Collaboration on Roadway Head - Mingkun Luo; Lei Yang; Haiou Wen; Dongsheng Zhao; Kun Wang (Geofluids)
In order to improve efficiency of gas drainage, the reasonable layout parameters for borehole on roadway head are investigated. Assuming that the coal mass has a dual pore structure with fractures and pores, a multiphysical field coupling mathematical model is proposed for gas drainage. The governing equations of gas adsorption, seepage, and diffusion are considered. The process of gas preextraction and excavating-extraction collaboration on roadway heading face in 2606 haulage roadway of Zhangcun mine is modeled by finite element (FE) method. The effects of gas drainage under different drilling arrangements are analyzed. The results show that the fastest decreasing rate of gas content occurs at the beginning of drainage, and decreasing rate of gas content tends to be stable in the later stage. After removing the predraining on roadway head, the gas content at the center of coal wall on the roadway heading face will rebound. The included angle between the borehole and the roadway middle line determines the spatial area of gas drainage. Too small included angle will reduce the area of gas content reduction, while too large included angle will result in a blind area on both sides of the roadway. The change in borehole spacing affects the decreasing rate of gas content in the rock and coal around the roadway. Large spacing may cause an inadequate decreasing rate in the middle of the roadway, while small spacing may cause an inadequate decreasing rate in both sides of the roadway. In the field application, the pure gas flow and gas concentration of drainage show a downward trend in whole. The gas concentration decreased from 13.2% to 10.8%, and the pure gas flow decreased from 10.6 m3/min to 8.15 m3/min. Research achievements can provide a basis for gas drainage in underground roadway.